Kaitan Karakteristik Kepala Rumah Tangga dengan Kemiskinan Anak di Nusa Tenggara Barat pada Tahun 2019 - Suci Ramadhanty; Hardius Usman (Seminar Nasional Official Statistics, 2021)
Poverty causes negative effects for children, both in the short and long term which risk depriving them of their future. West Nusa Tenggara (NTB) is one of the provinces that has a high poverty rate, and the age group most at risk for poverty is children. This study aims to study the effect of household head's characteristics on child poverty in ntb at 2019. This study uses the March 2019 Susenas data. By using the Binary Logistics Regression analysis method, this study finds that the number of Household Members, gender of household heads, employment status of household heads, and education level of household heads have a significant effect on child poverty. This study also revealed that poverty tends to be greater in children living with household heads with the number of household members > 4 people, female household heads, household heads who don't work, and household heads with low education.